2021
DOI: 10.1094/pdis-07-20-1447-re
|View full text |Cite
|
Sign up to set email alerts
|

Does Use of Atoxigenic Biocontrol Products to Mitigate Aflatoxin in Maize Increase Fumonisin Content in Grains?

Abstract: In the tropics and subtropics, maize and other crops are frequently contaminated with aflatoxins by Aspergillus flavus. Treatment of crops with atoxigenic isolates of A. flavus formulated into biocontrol products can significantly reduce aflatoxin contamination. Treated crops contain up to 100% less aflatoxins compared to untreated crops. However, there is the notion that protecting crops from aflatoxin contamination may result in increased accumulation of other toxins, particularly fumonisins produced by a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Some of the technologies composing the strategies designed by the Aflasafe Initiative (e.g., insect control, drying, appropriate storage) may also be effective to reduce accumulation of mycotoxins other than aflatoxins. Other solutions such as cultivars resistant to target mycotoxins could be incorporated in agronomic packages to reduce incidences of other mycotoxins that may co-occur along with aflatoxins in susceptible crops (Ortega-Beltran et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the technologies composing the strategies designed by the Aflasafe Initiative (e.g., insect control, drying, appropriate storage) may also be effective to reduce accumulation of mycotoxins other than aflatoxins. Other solutions such as cultivars resistant to target mycotoxins could be incorporated in agronomic packages to reduce incidences of other mycotoxins that may co-occur along with aflatoxins in susceptible crops (Ortega-Beltran et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…A concerning issue regards the potential promotion of fumonisin-producing strains and the possibility that non aflatoxigenic strains produce other mycotoxins in the field. Nonetheless, this hypothesis has not been yet verified ( Ortega-Beltran et al, 2021 ).…”
Section: Advanced Mycotoxin Reduction With Biological Controlmentioning
confidence: 99%
“…Large-scale production and the impact of such methods in actual application must be assessed ( Ortega-Beltran and Bandyopadhyay, 2021 ). Another critical point is that regulatory approval through a dossier submission to EFSA must be obtained.…”
Section: Advanced Decontamination Techniques To Minimize Aflatoxin Riskmentioning
confidence: 99%
“…Testing the technology in those scenarios may provide unpredictable results but that does not negate the effectiveness of the technology everywhere. Apart from the known effectiveness in the US Dorner, 2009;Doster et al, 2014;Grubisha and Cotty, 2015), over a decade of field effectiveness trials and commercial usage in various SSA countries has demonstrated that biocontrol products successfully limit aflatoxin in a wide range of environments and cropping conditions, predominantly within tolerance thresholds (Bandyopadhyay et al, 2019;Agbetiameh et al, 2020;Senghor et al, 2020Senghor et al, , 2021Mahuku et al, 2022;Ola et al, 2022). For example, nearly 100,000 ha of maize were treated in Nigeria during a 10-year period and most (>95%) of the >300,000 tons of harvested maize had <4 ppb total aflatoxin and, in general, treated crops contained >80% less aflatoxin than untreated maize.…”
mentioning
confidence: 99%
“…The available products developed following well-tested and rigorous processes are already effective, licensed, and commercialized. Farmers trust these products as they result in reduced aflatoxin contamination, a precursor for access to premium markets (Bandyopadhyay et al, 2019;Agbetiameh et al, 2020;Konlambigue et al, 2020;Senghor et al, 2020Senghor et al, , 2021Ola et al, 2022).…”
mentioning
confidence: 99%